Competing for influence: The role of the public service in better government in Australia - Barry Ferguson (ANU Press, 2019)
Amidst growing dissatisfaction with the state of government performance and an erosion of trust in our political class, Competing for Influence asks: what sort of public service do we want in Australia? Drawing on his experience in both the public and private sectors - and citing academic research across the fields of public sector management, industrial organisation, and corporate strategy - Barry Ferguson argues the case for the careful selection and application of private sector management concepts to the public service, both for their ability to strengthen the public service and inform public policy. These include competitive advantage, competitive positioning, horizontal strategy and organisational design, and innovation as an all-encompassing organisational adjustment mechanism to a changeable environment. But these are not presented as a silver bullet, and Ferguson addresses other approaches to reform, including the need to rebuild the Public Sector Act, the need to reconsider the interface between political and administrative arms of government (and determine what is in the 'public interest'), and the need for greater independence for the public service within a clarified role. This approach, and its implications for public sector reform, is contrasted with the straitjacket of path dependency that presently constricts the field.
Keywords: 300